High Sequence Variability, Diverse Subcellular Localizations, and Ecological Implications of Alkaline Phosphatase in Dinoflagellates and Other Eukaryotic Phytoplankton - Lin, Xin; Zhang, Huan; Cui, Yudong; Lin, Senjie (Frontiers in Microbiology, 2012)
Alkaline phosphatase (AP) is a key enzyme for phytoplankton to utilize dissolved organic phosphorus (DOP) when dissolved inorganic phosphorus is limited. While three major types of AP and their correspondingly diverse subcellular localization have been recognized in bacteria, little is known about AP in eukaryotic phytoplankton such as dinoflagellates. Here, we isolated a full-length AP cDNA from a latest-diverging dinoflagellate genus Alexandrium, and conducted comparative analyses with homologs from a relatively basal (Amphidinium carterae) and late-diverging (Karenia brevis) lineage of dinoflagellates as well as other eukaryotic algae. New data and previous studies indicate that AP is common in dinoflagellates and most other major eukaryotic groups of phytoplankton. AP sequences are more variable than many other genes studied in dinoflagellates, and are divergent among different eukaryotic phytoplankton lineages. Sequence comparison to the other characterized APs suggests that dinoflagellates and some other eukaryotic phytoplankton possess the putative AP as phoA type, but some other eukaryotic phytoplankton seem to have other types. Phylogenetic analyses based on AP amino acid sequences indicated that the “red-type” eukaryotic lineages formed a monophyletic group, suggesting a common origin of their APs. As different amino acid sequences have been found to predictably determine different spatial distribution in the cells, which may facilitate access to different pools of DOP, existing computational models were adopted to predict the subcellular localizations of putative AP in the three dinoflagellates and other eukaryotic phytoplankton. Results showed different subcellular localizations of APs in different dinoflagellates and other lineages. The linkage between AP sequence divergence, subcellular localization and ecological niche differentiation requires rigorous experimental verification, and this study now provides a framework for such a future effort.